2014
DOI: 10.1002/brb3.206
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cardiac perception predicts impaired performance in the Iowa Gambling Task in patients with panic disorder

Abstract: ObjectiveSomatic marker theory predicts that somatic cues serve intuitive decision making; however, cardiovascular symptoms are threat cues for patients with panic disorder (PD). Therefore, enhanced cardiac perception may aid intuitive decision making only in healthy individuals, but impair intuitive decision making in PD patients.MethodsPD patients and age-and sex-matched volunteers without a psychiatric diagnosis (n = 17, respectively) completed the Iowa Gambling Task (IGT) as a measure of intuitive decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…Interoceptive attentiveness may more broadly support optimal resource allocation for the comparison of such information against predictions. This could affect the quality of interoceptive information available for intuition-based decision-making and might affect or even hamper the development of somatic markers, which appears to be an issue in patients with panic disorder [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interoceptive attentiveness may more broadly support optimal resource allocation for the comparison of such information against predictions. This could affect the quality of interoceptive information available for intuition-based decision-making and might affect or even hamper the development of somatic markers, which appears to be an issue in patients with panic disorder [21].…”
Section: Discussionmentioning
confidence: 99%
“…From the view that interoception mediates between the perception of somatic states and domains that are highly relevant for successful coping with the challenges of everyday life, such as intuition, emotion and (decision) behaviour, it follows that improved understanding of the underlying functional anatomy may aid understanding and interventions for a wide array of issues including maladaptive response to somatic cues in panic disorder [21,33], somatoform disorder [34,35], dissociative disorders [36][37][38] or eating disorders [39,40]. Maladaptive stress reactivity in terms of cognitive and emotional response to issues in processing interoceptive information may contribute to poor somatic health [41].…”
Section: Introductionmentioning
confidence: 99%
“…As O/C symptoms are more likely to relate to a feared outcome and be motivated by a goal of reducing anxiety, they are more closely tied to traditional cognitive models of OCD and thus more closely resemble anxiety disorders (Coles, Pietrefesa et al, ; Starcevic & Brakoulias, ; Summerfeldt et al., ). There is evidence suggesting that anxiety influences decision‐making (Engelmann, Meyer, Fehr, & Ruff, ; Hartley & Phelps, ; Luhmann, Ishida, & Hajcak, ; Miu, Heilman, & Houser, ; Raghunathan & Pham, ), and is impaired in anxiety disorders (Teng et al., ; Wölk, Sütterlin, Koch, Vögele, & Schulz, ). Therefore, when taken into context of existing literature, the current results concerning decision‐making may suggest that the neural processes underlying O/C symptoms are similar to those seen in anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from neuropsychological literature also demonstrate similarities between deficits seen in individuals with tic disorders and the pattern of cognitive impairment related to S/O symptoms in the current study. Specifically, studies suggest that individuals with Tourette's syndrome show deficits related to cognitive flexibility (Bornstein, Baker, Bazylewich, & Douglass, ; Watkins et al., ) and visuospatial ability (Schultz, Evans, & Wolff, ). Similarly, greater deficits in visuospatial ability (Gruner, ) and cognitive flexibility (Gruner & McKay, ), have been found in individuals with OCD with tics compared to those with OCD without tics.…”
Section: Discussionmentioning
confidence: 99%
“…This forms the conclusion that the processing of interoceptive signals seems to be essential to improve memory consolidation under stress. Another point concerning the psychophysiology behind cortisol and interoception is that different studies showed that a higher IAcc resulted in better decision processes (Werner, Jung, Duschek, & Schandry, ; Wölk et al, ). Regarding stress, it was found that executive functions decreased under stress, which could be an indicator for diminished decision making that is caused by an increased cortisol level (Koot, Baars, Hesseling, van den Bos, & Joëls, ; van den Bos, Harteveld, & Stoop, ).…”
Section: Discussionmentioning
confidence: 99%